Relationship Between Mother's Knowledge Levels About Food Assisted With Association With Timeliness Of Giving - Ayu Andhira; Safruddin; Tenriwati; Haerati (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2020)
Complementary feeding should be given after the baby is 6 months old because it can provide great benefits to the baby (Kodrat, 2010). Factors that play an important role in preventing improper complementary feeding are the mother's knowledge and work factors. Mother's behavior in this case plays an important role in preventing improper complementary feeding so that it will reduce the risk of the baby experiencing digestive disorders and can have a stronger immune system. Some mothers do not provide complimentary foods on time. To find out the relationship between the level of knowledge of mothers about complementary foods with the timeliness of complementary feeding in the working area of ​​Puskesmas Caile. This type of research is a quantitative study using a non-experimental design using a cross-sectional approach. The sample of this study was 49 respondents who were taken by consecutive sampling method. The data analysis in this study used the chi-square test statistical test. Based on the results of univariate analysis, it is known that the knowledge of mothers about complementary feeding is at the most sufficient and good categories as many as 44 people (67.7%). And the timeliness of giving complementary foods was in the most precise category as many as 38 people (58.5%). The results of the analysis using the chi-square test obtained a significant value of 0.001 (p <0.05). There is a relationship between the level of knowledge of mothers about complementary foods with breastfeeding and the timeliness of complementary feeding. And it is suggested that the hospital institution is expected to consider its implementation as nursing care regarding the relationship between the level of knowledge of mothers about complementary foods with breastfeeding and the timeliness of complementary feeding.